Surveying Industrial Clusters: A comprehensive Bibliometric Account - Cruz, Sara Cristina Santos (2007)
As the global paradigm became an accepted reality, the local dimension has gained particular interest as an object of analysis. This is because key factors of global competitiveness have become deeply rooted at a local level. In this context, clusters, as geographical and socio-relational entities with a specific evolutionary path, institutional embeddedness and local knowledge dynamics, have become crucial elements in regional development, assuming a significant role in public policies. Despite its growing importance, the concept of cluster has been subject to a rather discretionary use in terms of interpretation and meaning. Since the multiplicity of definitions has flourished with the historical evolution of the cluster concept, it became necessary to find a way to organize the existing literature, in an attempt to overcome this multitude of notions and meanings. This dissertation aims to systematize the existing corpus of theoretical approaches and empirical studies on clusters by carrying out a thorough, qualitative survey of the cluster literature, complemented with a comprehensive bibliometric account, based on articles published in journals indexed in the Econlit and EBSCO bibliographic databases, from 1962 to 2007. The main outcomes of this research show that besides their importance in academic fields, the role of clusters has also been widely acknowledged in political spheres. Along with an increasing interest in the `local dimension, an emergent corpus of literature on global networks and clusters has also arisen. Moreover, behind the recent boom in the cluster literature is the influence of the prominent themes `local networks and social approaches and `knowledge-based theories . Studies on `regional and national innovation systems and `institutional approaches (mostly concerned with enrooted local cultures, governance and customs) have been achieving a particular importance since the 1990s. This clearly reflects the most recent trends in the cluster literature, which focus particularly on `systemic and `institutional factors. Finally, despite the positive correlation between the `quality of journals and related formal research, the evolution of the literature on clusters continues to be mostly appreciative-led.